PEMBERDAYAAN MASYARAKAT KELURAHAN BENOA MELALUI PROGRAM KKN UNTUK MEWUJUDKAN MASYARAKAT YANG SEHAT DAN INOVATIF - Pratiwi, M.A. (Buletin Udayana Mengabdi, 2023)
The global COVID-19 pandemic has brought many changes, especially to the health conditions of the world community and economy. A very crucial impact in the province of Bali is the decline in public health and many family heads have lost their jobs. This resulted in a very significant decline in public health and welfare. The community of Benoa Village, Bali is one of the many villages experiencing a decline in health and welfare. One of the efforts that can be made to improve welfare is through the "Community Empowerment of Benoa Village through the Community Service Program to Create a Healthy and Innovative Community". The purpose of this community empowerment activity is to improve the health and welfare of the community through health and socio-economic programs in KKN (Community Service Program) activities. This community empowerment activity is carried out in 3 programs, namely public health and environmental health programs, socio-economic programs, and assistance programs. The method of implementing the program is through socialization, training and counseling to the community The results of the work programs of the three fields are that they can be implemented well and get a positive response from the community. In addition, there are 2 aid programs including 1) Education of local materials to increase hemoglobin with the South Kuta Health Center, and 2) Assisting with plastic exchange activities that have been carried out well. Keywords: Health and Environment Sector, Socio-Economic Sector, Benoa Village, Community Empowerment, Healthy and Innovative Society